Implementation of K-Means Algorithm and C4.5 Classification in the Analysis of Determinants of Student Timely Graduation - Rahma Yanti; Musli Yanto; Syafri Arlis (Universitas Putra Indonesia YPTK Padang, 2026)
This study was motivated by the importance of timely graduation as a key parameter affecting program accreditation. The timely graduation rate reflects the effectiveness of academic management and serves as an indicator of program quality. The purpose of this study was to apply the concept of data mining using the K-means and Decision Tree C4.5 methods to analyze the timely graduation of students in the Information Technology and Computer Education Study Program at UIN Bukittinggi. The research methods used are the K-Means and Decision Tree C4.5 methods. The K-Means algorithm is used to cluster student graduation data, which will then be processed in the next method. The Decision Tree C4.5 algorithm is used to classify student graduation data. The research data was sourced from the 2017 batch of the Information Technology and Computer Education Study Program at UIN Bukittinggi, with a total of 158 data points. The results of this study produced a model that was able to achieve an accuracy rate of 96% in the validation process. The accuracy results were relatively high, so the model produced can be used by the study program to improve academic quality. Based on the results of this study, it contributes as a basis for evaluating student academic performance, monitoring the risk of study delays, and supporting academic decision-making. In addition, this information contributes to maintaining and improving academic quality and supports the achievement and maintenance of the accreditation status of the PTIK UIN Sjech M. Djamil Djambek Bukittinggi Study Program.